KEMAMPUAN SISWA KELAS VII SMP NEGERI 35 PADANG MENULIS KEMBALI DONGENG YANG DIPERDENGARKAN - Fitria, Nuzul; Nisja, Indriani; Marni, Silvia (Pendidikan Bahasa Indonesia, 2014)
This research was conducted due to the studentsâ difficulties in expressing their ideas when they were asked to write tales .this researcsh was designed for describing the studentsâ ability in rewriting spoken tales in class VII of SMP Negeri 35 Padang. This was aÂ aquantitative research which used descriptive method. The data of the research was gotten from a test. The result of the research showed that the studentsâ ability in rewriting the spoken tales in class VII of SMP negeri 35 Padang was good in which the studentsâ average score was 81,94%. The studentsâ ability in rewriting theÂ rewriting the spoken tales viewed from (1) plot was good inÂ which the studentsâ average score was 77,08%,(2) background was very good in which the studentsâ average score was 86,45%, (3) characters was good in which the studentsâ average score was 82,29%. Based on these results , it was concluded that the ability of the stundentsâ in class VII of SMP Negeri 35 Padang in rewriting the spoken tales was good in which the students average score was 81,94%.